PS-003 Safety and economic outcome after implementation of a restricted use antibiotic protocol. (14th February 2016) - Tevar, E; De León-Gil, A; Febles, JC; Betancor-Garcia, T; Plasencia-Garcia, I; Ocaña-Gomez, MA; Ramos-Linares, S; Díaz, P; Marqués, E; Merino, J
Abstract : Background: In 2013, our protocol of restricted use antibiotics (RUA) was updated and computerised. The following drugs were subject to their respective indications. Ertapenem: community intra-abdominal infection with risk factors, moderate or severe diabetic foot infections and outpatient management. Linezolid: pneumonia, diabetic foot infections, osteomyelitis and prosthetic infections, and serious bile duct infections. Daptomycin: endocarditis, diabetic foot infections, osteomyelitis and prosthetic infections, and right sided endocarditis. Tigecycline: complicated intra-abdominal infections or soft tissue infections, except diabetic foot infections, if there is no alternative. Purpose: To evaluate RUA outcomes 1 year after implementation. Material and methods: Computerised orders received in 2013; retrospective analysis. Results: 500 requests for RUA were conducted: 22% ertapenem, 37.2% linezolid, 35.2% daptomycin and 5.6% tigecycline. The antibiotics were used as follow: ertapenem: intra-abdominal infections in 50.91%, diabetic foot infections 15.45%, peritonitis 9.1% and 27 patients (24.54%) to promote outpatient management. Linezolid: 32.26% skin and soft tissue infections, 30.12% pneumonia, 13.5% biliary tract infections, 9.6% osteomyelitis and prosthesis infections and 6.99% in diabetic foot infections. Daptomycin: 42.61% in infections of skin and soft tissues, 18.79% in bacteraemia, 13.07% in endocarditis, 10.8% in biliary tract infections; for hospital management, osteomyelitis and prosthetic infections, and diabetic foot infections were requested in 13.7% and 6%, respectively. Tigecycline: 11 cases of intra-abdominal infection and 17 skin and soft tissue infections. The RUA spending in 2013 compared with the previous year decreased by €31 843. Daptomycin increased slightly (€1461) while consumption of tigecycline and ertapenem was reduced by €14 254 and €13 131, respectively. This was a 45.7% and 31.5% reduction in costs over the previous year. Linezolid spending was also reduced €5920, slightly over (2%) the previous year. Conclusion: The update and computerisation of the RUA protocol has achieved a reduction in spending on these antibiotics and improved adjustment of the prescriptions to the current indications for these drugs. References and/or Acknowledgements: Hospital Computing Service. No conflict of interest.